Detecting Heritage Crime(s): What We Know about Illicit Metal Detecting in England and Wales. Issue 2 (May 2019) - Daubney, Adam; Nicholas, Louise E.
Abstract: Metal detecting is a popular hobby in England and Wales, and, since 1997, over 1.3 million finds have been recorded by the Portable Antiquities Scheme (PAS), a scheme to encourage the voluntary recording of artifacts found by the public. The metal detector can be a useful archaeological tool when used lawfully and responsibly; however, it is also a tool that is used for illicit purposes by individuals and groups wishing to obtain artifacts from archaeological sites on which they have no permission to detect. Information on the number and nature of incidents of illicit metal detecting, however, is difficult to collate owing both to the nature of the crime and to the way it is recorded (or not) by law enforcement authorities. In this article, we examine the strengths and limitations of the available official and unofficial sources on illicit metal detecting in England and Wales and explore the potential they have to tell us about current trends in this form of heritage crime. The first unofficial source is a list of incidents reported to Historic England, which contains basic information on 276 incidents recorded between 2010 and 2017. The second source is the result of a survey of the PAS's finds liaison officers regarding the extent to which they assisted law enforcement authorities for the years from 2015 to 2017. Both sources were then contrasted with a freedom of information request that was sent to all 49 police forces in the United Kingdom. Although there are some synergies between the unofficial and official sources, the lack of detail in any one dataset makes them of limited use in demonstrating trends in the macro- and micro-scales of time and place. Accordingly, many of the issues highlighted in this article could be resolved by devising a better system for police record keeping of metal detecting offences.